Social and Emotional Skills of children with ASD: Assessment with Emotional Comprehension Test (TEC) in a Greek context and the role of ICTs - Chaidi, Irene; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
Children on the autism spectrum have significant difficulties in recognizing, I understanding, and expressing emotions and and consequently in their socialization [1], [2] [3] [4] [5] . To assess the ability to understand emotions, the following is used: The emotion comprehension test (Test of Emotional Comprehension, TEC ) [6] in preschool children. In the present work, the TEC was administered to students with ASD and the results of the evaluation are analyzed and conclusions are drawn.